Membentuk Ketahanmalangan Anak di Lingkungan Sekolah Melalui Permainan Tradisional - Ratri Nuria; Muhammad Zainal Abidin (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Efforts to optimize children's development are based on strengthening children's resilience to adversity. One way to build children's resilience is by facilitating children to play outdoors, namely through traditional games. In this research, traditional games were limited to Gobak Sodor and Skipping Rope by examining 25 children aged 5-7 years. The research was carried out in 2 cycles to get results on indicators (1) Solving problems independently, the results of cycle 1 were 63%, while the results of cycle II were 97%; (2) Not giving up easily, the results in cycle I were 67%, while in cycle II it was 94%; (3) Hardiness results in cycle I were 67%, while in cycle II it was 93%; (4) Liked the challenge, getting results in cycle I was 65%, while in cycle II it was 98%; (5) Dare to take risks and the results in cycle I were 68%, while in cycle II the results were 95%.Efforts to optimize children's development are based on strengthening children's resilience to adversity. One way to build children's resilience is by facilitating children to play outdoors, namely through traditional games. In this research, traditional games were limited to Gobak Sodor and Skipping Rope by examining 25 children aged 5-7 years. The research was carried out in 2 cycles to get results on indicators (1) Solving problems independently, the results of cycle 1 were 63%, while the results of cycle II were 97%; (2) Not giving up easily, the results in cycle I were 67%, while in cycle II it was 94%; (3) Hardiness results in cycle I were 67%, while in cycle II it was 93%; (4) Liked the challenge, getting results in cycle I was 65%, while in cycle II it was 98%; (5) Dare to take risks and the results in cycle I were 68%, while in cycle II the results were 95%.